Solid Business Contracts: Understanding the Legal Aspects of a Deal - Panjaitan, Wijaya Natalia; Nabila, Syadzwina Hindun (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The development of an increasingly complex business world makes contracts function as the main tool to regulate the rights and obligations of the parties involved in an agreement. Therefore, understanding and skills in drafting business contracts are very important as a foundation in helping the parties bound by the contract.Purposes of The Devotion: To educate the public on the legal aspects of the agreement as a solid business contract. Method of The Devotion: The devotion method used is the method of counseling and mentoring the community of Jambi city with the Pranata Iustitia Jambi Legal Aid Institute.Results Main Findings of the Devotion: A strong contract does more than just help minimize the risk of conflict, it also ensures that the deal is legally enforceable.